As relações entre política e vida: o problema do poder em Hannah Arendt e Michel Foucault - Oliveira Filho, João Francisco Gabriel de (2014)
This dissertation investigates proximities and distances of the political analyses made by Hannah Arendt and Michel Foucault. It is intended to comment the relationships between philosophy and politics in antiquity, discussed by these authors, and, envision effects of these relationships which culminated in the government of the men in the Christian age. After that, it is intended to conjecture how, in the modern context, the biological life became a preoccupation in politics. Thus this work tries to identify their different approaches to power and problematize these approaches in their typical ways of considering politics and the theme of origin